2000
DOI: 10.17705/1jais.00005
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Adoption of Internet Banking

Abstract: A research framework based on the theory of planned behavior (Ajzen 1985) and the diffusion of innovations theory (Rogers 1983) was used to identify the attitudinal, social and perceived behavioral control factors that would influence the adoption of Internet banking. An online questionnaire was designed on the World Wide Web (WWW). Respondents participated through extensive personalized email invitations as well as postings to newsgroups and hyperlinks from selected Web sites. The results revealed that attitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

70
783
11
35

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,017 publications
(1,039 citation statements)
references
References 36 publications
(34 reference statements)
70
783
11
35
Order By: Relevance
“…The use ATMs now belong firmly in the "modern" way of doing things. The significant contribution of Compatibility to the DOI model was also highlighted in other studies particularly those of Chen et al (2002) and Tan and Teo (2000).…”
Section: Test Of Hypothesessupporting
confidence: 63%
See 3 more Smart Citations
“…The use ATMs now belong firmly in the "modern" way of doing things. The significant contribution of Compatibility to the DOI model was also highlighted in other studies particularly those of Chen et al (2002) and Tan and Teo (2000).…”
Section: Test Of Hypothesessupporting
confidence: 63%
“…The Observability construct was not simply about watching others using the technology, but (as the results from the factor analysis revealed) involved perception and discernment, usually brought on by the influence of others ( in this case, other ATM users probably known to potential and new adopters). Other studies have shown the contribution of Observability to the DOI model (Tan and Teo, 2000;Taylor & Todd, 1995).…”
Section: Test Of Hypothesesmentioning
confidence: 97%
See 2 more Smart Citations
“…Las ventajas relativas deben tener una relación positiva con la tasa de una innovación de la adopción ( [11] y [12]). Esta dimensión dentro del sector financiero es importante.…”
Section: Factor Actitudunclassified